A Review Article on Basic Modern Algebra and Its Applications: Exploring the Fundamentals and Applications of Abstract Algebra (Journal of Advances and Scholarly Researches in Allied Education, 2018)
To find and study applications of abstract algebra, a certain amount of mathematical maturity is necessary. A fundamental knowledge of set theory, mathematical induction, complementarity and matrices is a must. The ability to read and understand mathematical evidence is even more important. In this chapter we will describe the background for an abstract algebra course. As well as we look at fundamental modern algebra and its applications.